Police and Thieves in the Stadium: Measuring the (Multiple)Effects of Football Matches on Crime - Olivier Marie
During large sporting events criminal behaviour may be affected via three main channels: (i) fan concentration, (ii) self incapacitation, and (iii) police displacement. In this paper I exploit information on football (soccer) matches for nine London teams linked to detailed recorded crime data at the area level to empirically estimate these different effects. My findings show that only property crime significantly increases in the communities hosting football matches but that they experience no changes in violent offences. These results are robust to controlling for a large number of game type and outcome characteristics. There is no evidence of temporal displacement of criminal activity. Our conceptual model suggests that the away game attendance effect on crime is due to voluntary incapacitation of potential offenders. I argue that the police displacement effect of hosting a match increases property crime by 7 percentage point for every extra 10,000 supporters.Football, police, crime